2022
DOI: 10.1017/jfm.2022.408
|View full text |Cite
|
Sign up to set email alerts
|

The separation angle of the free surface of a viscous fluid at a straight edge

Abstract: We rework some of the die-swell singularity analysis for Stokes flow, originally by Ramalingam (Ramalingam, 1994 Fiber spinning and rheology of liquid-crystalline polymers, PhD thesis, Massachusetts Institute of Technology) in appendix A of his PhD thesis, in an attempt to demonstrate that for capillary numbers in the range $(0,\infty )$ the curvature may enter into the normal stress balance on the free surface and lead to separation angles exceeding $180^{\circ }$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
5
6
0
Order By: Relevance
“…Since that time there has been widespread disagreement, both in the experimental and numerical literature, about the character of the free surface (and therefore about the solution to the problem) in the neighbourhood of the channel orifice and, in particular, about the angle of separation. The values of the separation angles computed by Owens [14] for capillary numbers Ca ranging from 1 to 1,000 fell well within the interval of values published in previous experimental and numerical papers, although there is a paucity of such results available in the literature. His analysis showed that for non-zero surface tensions the normal stress and curvature of the free surface were unbounded at the point of separation, consistent with the analysis and results of Anderson and Davis [15], Schultz and Gervasio [16] and Salamon et al [17].…”
Section: Bims For Boundary Value Problems With Singularities On the B...supporting
confidence: 85%
See 4 more Smart Citations
“…Since that time there has been widespread disagreement, both in the experimental and numerical literature, about the character of the free surface (and therefore about the solution to the problem) in the neighbourhood of the channel orifice and, in particular, about the angle of separation. The values of the separation angles computed by Owens [14] for capillary numbers Ca ranging from 1 to 1,000 fell well within the interval of values published in previous experimental and numerical papers, although there is a paucity of such results available in the literature. His analysis showed that for non-zero surface tensions the normal stress and curvature of the free surface were unbounded at the point of separation, consistent with the analysis and results of Anderson and Davis [15], Schultz and Gervasio [16] and Salamon et al [17].…”
Section: Bims For Boundary Value Problems With Singularities On the B...supporting
confidence: 85%
“…It is shown in Section 4.1 that for any given surface tension, the (positive) slope of the free surface attains a maximum near the separation point and that the second derivative grows dramatically as the separation point is approached along the free surface, the curvature at the separation point itself being infinite. In Section 4.2 we present results for the extrudate swell ratio over a range of capillary numbers and these are shown to be in excellent agreement with others in the numerical literature [14], [17], [19], [25]. However, recognising that the extrudate swell ratio is a somewhat crude measure of the correctness of the solution, in Section 4.3 we also post our calculated values for the separation angles α and leading order indices λ 1 appearing in the asymptotic forms of the flow variables in the immediate neighbourhood of the separation point.…”
Section: Outlinesupporting
confidence: 77%
See 3 more Smart Citations